Anatomical patterns of biliary atresia including hepatic radicles at the porta hepatis influence short‐ and long‐term prognoses. (1st July 2021) - Sasaki, Hideyuki; Nio, Masaki; Ando, Hisami; Kitagawa, Hiroaki; Kubota, Masayuki; Suzuki, Tatsuya; Taguchi, Tomoaki; Hashimoto, Takashi; ,
Abstract: Background/Purpose: The biliary atresia (BA) inflammatory process leads to various obstructive patterns of extrahepatic biliary trees. The significance of the various BA obstructive patterns is unclear. This study aimed to determine the relationship between the anatomical patterns of the biliary tract and short‐ and long‐term prognoses in BA. Methods: Between 1989 and 2018, 3483 patients were registered in the Japanese Biliary Atresia Registry. For this study, we selected 2649 patients who underwent Kasai portoenterostomy (KP) between the ages of 31 and 90 days to eliminate the influence of age at KP as much as possible. Results: Regarding the main type, there were significant differences in the jaundice clearance rate (JCR; Type I: 67.9%, Type I‐cyst: 79.4%, Type II: 74.5%, Type III: 60.9%; P  < .0001) and the native liver survival rate (NLSR; P  < .0001). In subgroups with hepatic radicles in Types I, II, and I‐cyst, there was a significant difference in JCR ( P  = .0004) and NLSR ( P  = .0026). In subgroups with hepatic radicles in Type III, there was a significant difference in JCR ( P  = .0148) and NLSR ( P  = .0421). Conclusions: Anatomical patterns of obstruction influenced short‐ and long‐term prognoses in BA. These patterns were suggested to be prognostic factors following KP. Abstract : Highlight Sasaki and colleagues examined the relationship between the anatomical patterns of the biliary tract and prognosis in biliary atresia using data from the Japanese Biliary Atresia Registry. Anatomical patterns of obstruction influenced short‐ and long‐term outcomes in biliary atresia. These patterns were suggested to be prognostic factors following Kasai portoenterostomy.